PRC2 functions in development and congenital disorders - Deevy, Orla (Development, 2019)
Polycomb repressive complex 2 (PRC2) is a conserved chromatin regulator that is responsible for the methylation of histone H3 lysine 27 (H3K27). PRC2 is essential for normal development and its loss of function thus results in a range of developmental phenotypes. Here, we review the latest advances in our understanding of mammalian PRC2 activity and present an updated summary of the phenotypes associated with its loss of function in mice. We then discuss recent studies that have highlighted regulatory interplay between the modifications laid down by PRC2 and other chromatin modifiers, including NSD1 and DNMT3A. Finally, we propose a model in which the dysregulation of these modifications at intergenic regions is a shared molecular feature of genetically distinct but highly phenotypically similar overgrowth syndromes in humans.